Smart metering interoperability issues and solutions: Taking inspiration from other ecosystems and sectors. (June 2022) - Reif, Valerie; Meeus, Leonardo
Abstract: Interoperability in the context of smart electricity metering is high on the European policy agenda, but its essence has been challenging to capture. This paper looks at experiences in other ecosystems (electromobility and buildings), in other sectors (healthcare and public administration), and at the national level in the Netherlands and the UK. We show that the definition of interoperability depends on the context, that there are common solutions to different issues across sectors and that cross-sectoral factors must be increasingly considered. We recommend adopting a broader view in smart metering beyond the interoperability of devices, considering solutions that have worked in other sectors and exploiting synergies across sectors. Our analysis of experiences provides a comparison that can help move the debate at the EU level forward. Highlights: The EU implementing acts are an opportunity to tackle interoperability issues related to smart electricity metering. We recommend giving more attention to the non-technical aspects of interoperability. The organisation of interoperability, including the roles and responsibilities of the involved actors, still needs to be addressed. We also recommend considering solutions that have worked in other sectors. Examples are an EU monitoring and reporting scheme for national interoperability progress (as in public administration) or a scheme for interoperability testing (as in healthcare).